Alteration of mesenchymal stem cells polarity by laminar shear stimulation promoting β-catenin nuclear localization. (January 2019) - Chen, Wei-Ta; Hsu, Wei-Tse; Yen, Meng-Hua; Changou, Chun A.; Han, Chia-Li; Chen, Yu-Ju; Cheng, Ji-Yen; Chang, Tzu-Hao; Lee, Oscar Kuang-Sheng; Ho, Jennifer Hui-Chun
Abstract: Mesenchymal stem cell (MSC) is mechanosensitive and the respond to mechanical force is pattern specific. We previously reported that oscillatory shear stress at 0.5 ± 4 dyne/cm 2 guided MSCs polarity vertical to net flow direction before apolaric stage at 30 min resulting in phosphorylation of β-catenin and inhibition of Wnt signaling. This time, we explored laminar shear stress (LS) at 0.5 dyne/cm 2 polarized MSCs by guiding F-actin orientation parallel to the flow direction before apolarity at 30 min accompanied with activation of Wnt signaling. Time-dependent microarray analysis supported cell-cell junctional complex of MSCs was the major mechanosensor on MSCs to respond 0.5 dyne/cm 2 LS. Three-dimensional immunofluorescence image confirmed LS promoting β-catenin nuclear localization during 15 min to 1 h with a peak at 30 min. Functional analysis of proteomic study on MSC with 30 min LS stimulation indicated that upregulation of β-catenin downstream proteins related to cardiovascular development, endothelial cell protection and angiogenesis. Conditioned medium from MSCs with 30 min LS stimulation improved the viability of human endothelial cells from oxidative damage. In conclusion, 0.5 dyne/cm 2 LS on MSCs for 30 min guides MSCs lack of polarity and promotes β-catenin nuclear translocation favoring Wnt activation and paracrine cardiovascular support.